Attitude of Farm Families towards Gender Equity: Development and Validation of a Scale - Bhati, Khushboo; Maulika J. Patel,; R.D. Pandya, (Indian Journal of Extension Education, 2023)
Gender equity is the means to achieve gender equalities in farm families. According to their respective needs based on equivalency in terms of rights, benefits, obligations, and opportunities are considered fair in the treatment of farm women and farmers. Thus, it was very essential to measure the favorableness of farm families toward gender equity. It measures to reflect their acceptance and thought process regarding present gender dynamics in their house and farm. The present study focussed to devise an instrument and for that, a Likert’s Summated rating technique was used in the year 2022 with a true standardized methodology to construct the attitude towards gender equity. A total of 94 items were constructed by reviewing related literature. Based on the 80 responses from experts, 16 items were screened through item analysis. A split-half technique was used to measure the reliability of the scale and the reliability coefficient was 0.861. The validity of the scale was also proved as per experts’ judgments.